Glaciers, Rivers, and Springs A Water Sector Diagnostic of Nepal - Joseph, George (Water Papers, 2022)
Nepal is rich in water resources with a dense network of glaciers, lakes, rivers, and springs that originate in the Himalayas. However, only an estimated 15 billion cubic meters (BCM) of the 225 BCM water available annually is utilized for economic and social purposes. Several elements have contributed to this low rate of utilization, including Nepal's rugged geography, inadequate institutional capacity, a history of prolonged political instability, and highly skewed seasonality - more than 80 percent of the precipitation in a year falls within a span of four months. For sustained economic growth and poverty reduction, and to enhance shared prosperity, Nepal must increase its investments in water-related infrastructure and institutions and improve the effectiveness of these investments. Although there is much to be done to harness this vital resource, it is important to broaden the development focus and integrate hydropower in a larger water resource management strategy. This strategy will ensure that water is available for basic and economic needs - even through the dry season - as a core component of Nepal's overall development plan. Given Nepal's development context and challenges, this document aims to analyze the most pressing sector challenges and identify strategic sector priorities that are aligned with the country's partnership framework. It offers a snapshot of water in Nepal's development story and situates the water sector in the broader context of the national economy, highlighting the importance of managing water resources for sustained economic growth and poverty reduction. It then presents five pressing sector-related challenges and concludes with a set of priority areas